2019
DOI: 10.1080/13691058.2019.1674920
|View full text |Cite
|
Sign up to set email alerts
|

The push of stigma: a qualitative study on the experiences and consequences of sexuality stigma among same-sex attracted men in Harare, Zimbabwe

Abstract: This paper describes experiences of sexuality stigma among same-sex attracted men in Zimbabwe and analyses the consequences of such experiences for healthcare seeking. It draws on qualitative research carried out in Harare in 2017, which included in-depth interviews with sixteen gay and bisexual men, and key informant interviews with three representatives of organisations that work with gay men. There were numerous stories about sexuality stigma in the study participants_ social environments, including at home… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Similarly, findings from a qualitative study describing the experience of MSM accessing HIV services in Bulawayo, Zimbabwe indicated that MSM who disclosed their sexual orientation often experienced stigmatization by healthcare providers, leading to fear of seeking services [51]. While mitigating healthcare-related stigma is critical, as Mutanga and Moen describe in their 2019 qualitative analysis of sexuality-related stigma among gay and bisexual men in Zimbabwe, reducing stigma among SGMs in this context requires multifaceted interventions targeting stigma at the individual, community, and government levels [25]. A combination intervention focused on SGM's access to healthcare, social perceptions of SGM, and the legal context surrounding non-heterosexual relationships in Zimbabwe will likely be more effective than either a universal or unidimensional approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, findings from a qualitative study describing the experience of MSM accessing HIV services in Bulawayo, Zimbabwe indicated that MSM who disclosed their sexual orientation often experienced stigmatization by healthcare providers, leading to fear of seeking services [51]. While mitigating healthcare-related stigma is critical, as Mutanga and Moen describe in their 2019 qualitative analysis of sexuality-related stigma among gay and bisexual men in Zimbabwe, reducing stigma among SGMs in this context requires multifaceted interventions targeting stigma at the individual, community, and government levels [25]. A combination intervention focused on SGM's access to healthcare, social perceptions of SGM, and the legal context surrounding non-heterosexual relationships in Zimbabwe will likely be more effective than either a universal or unidimensional approach.…”
Section: Discussionmentioning
confidence: 99%
“…In Zimbabwe, male-to-male sexual contact is criminalized and SGM stigma has been documented [24,25], although few studies have addressed psychosocial determinants of health among Zimbabwean SGM. Zimbabwe has a generalized HIV epidemic, with a prevalence of 12.9% among adults aged 15 years and older [26].…”
Section: Introductionmentioning
confidence: 99%
“…In our sample, TGW/GQ overall were more likely to have taken PrEP compared to their male counterparts and TGW/GQ in Harare and Bulawayo were more aware of PrEP than MSM in Bulawayo though awareness among TGW/GQ in both cities was comparable to that of MSM in Harare; this may be attributable to the larger KP program in Harare where funding and targets are greater than those in Bulawayo. A “one size fits all” approach to demand creation messaging is insufficient and our findings emphasize the need for tailored interventions to promote PrEP among KP; these may include advertisements through social media applications, dating applications and other online platforms considering sensitivities in this context, including criminalization of sex between men, homophobia and transphobia, and little to no legal protections for these groups [ 4 , 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, MSM and TGW have 22 and 12 times higher risk of HIV acquisition, respectively, than men in the general population and together, represent nearly 20% of all new HIV infections [3]. In Zimbabwe, where same-sex sexual relations are illegal and highly stigmatized [4,5], HIV prevalence among MSM, TGW and genderqueer/non-binary individuals (GQ) assigned male at birth is more than two times that of the general adult male population in urban areas (Harare: 21.4% vs. 10.0%; Bulawayo: 23.4% vs. 13.8%) and recent HIV infection among them is 1.1% [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…This was exempli ed by Mutambare et al who found that, in Gweru, people living with HIV defaulted on medication use because they believed in faith healing, alternative medicines, and perceived spirituality as the main cause of HIV and AIDS (9). Other studies are limited to describing the role of religious stigma (10), religious norms associated with sexuality and gender (11,12,13,14,15), and the belief in witchcraft as the spiritual source of illness and health (16). Finally, Shoko points to the signi cance of traditional beliefs and practices by explaining that traditional medicine is important to Shona people because it addresses aspects which bio-medical practice fails to (17).…”
Section: Introductionmentioning
confidence: 99%